Association of multidimensional frailty and dynapenia with fall risk in older adults - Maryam Ghorbanzadeh; Afsaneh Bakhtiari; Karimollah Hajian-Tilaki; Maryam Abbaszadeh-Amirdehi (BMC Geriatrics)
Abstract Background Dynapenia and frailty are known to be strong predictors of decreased function and increased mortality in the older adults. However, limited research on the co-occurrence of these factors and the different frailty domains makes their relationship with fall risk poorly understood. The aim of this study was to investigate the relationship between fall risk, dynapenia phenotypes, and frailty domains in the older adults. Methods In this cross-sectional study of 400 outpatients aged 65+, without major functional, cognitive, or serious comorbid issues, fall risk was assessed using the Berg Balance Scale. Frailty was evaluated via the TFI across physical, psychological, and social domains. Handgrip dynamometry determined dynapenia, classifying the participants into robust, dynapenic, abdominally obese, and dynapenic-obese phenotypes. To examine the associations between frailty, dynapenia, and fall risk, we applied a comprehensive, multi-layered analytical strategy covering all plausible combinations. Associations were analyzed using univariate and multivariate regressions in SPSS v23. Results In univariate analyses, fall risk was markedly higher among older adults with dynapenia (59.2%) or multidimensional frailty (60%), and peaked when both conditions coexisted (67.9%). Multivariate models demonstrated that dynapenia (OR = 2.75; 95% CI: 1.48–5.12) and frailty (OR = 2.56; 95% CI: 1.39–4.70) were independently associated with increased fall risk, with a pronounced effect when both were present (OR = 20.45; 95% CI: 6.02–46.69). Among frailty components, only physical (OR = 1.39; 95% CI: 1.19–1.62) and social frailty (OR = 1.38; 95% CI: 1.03–1.84) remained significant predictors in adjusted analyses. Interaction effects revealed that combining dynapenia with these domains further heightened the risk. A clear dose-response pattern emerged: fall risk escalated from 3.24-fold (95% CI: 1.48–3.09) with two frailty domains plus dynapenia, to 7.27-fold (95% CI: 3.46–7.29) when all three domains co-occurred. Conclusion Dynapenia and frailty, particularly in physical and social domains, independently and jointly elevate fall risk in older adults. Their co-occurrence demonstrates a dose-dependent effect, underscoring the need for integrated assessments to better identify and manage those at highest risk.